DENTAL X-RAY RADIATION EXPOSURE IN RADIOPROTECTION CASES AND DENTAL IMAGES REPEATABILITY FACTORS - Asmiati Amir; Muhammad Yunus; Septiana Kurniasari; Citron Supu Payu (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This research was carried out using a literature review method to determine radioprotection cases and repeatability factors of dental images on dental X-rays. Determination of the repeatability factor for dental photographs using data over three months obtained at Rajawali Citra Hospital, RSUD Dr. Tjitrowardojo Purworejo, and RSUD Muntilan Magelang. Case A, case B, and case C produce high percentage values. This is because dental practitioners consider the provision of protection in reducing the scattered dose of dental X-rays for patients to be often overlooked. Determination of X-ray radiation exposure given by a radiographer does not have significant differences for each patient, such as thin, standard, and obese. Meanwhile, the data on the percentage value of repetition of dental images exceeds the Minimum Hospital Service Standard indicator limit by the Decree of the Minister of Health Number 129 of 2008 concerning the incidence of X-ray service failure, which has a photo failure standard of ≤ 2%. The highest position factor was obtained at Hospital-2 at 75%, and the lowest was obtained at Hospital-1 at 50%. Meanwhile, the highest exposure factor was obtained at Hospital-1 at 39% and the weakest at Hospital-2 at 25%. Position errors made by the radiographer cause position factors, and exposure errors are caused by exposure factors that are too high or low.